Study of Ink‐Jet Printable Vinyl Ether‐Graphene UV‐Curable Formulations. Issue 3 (18th December 2014) - Sangermano, M.; Sturari, M.; Chiappone, A.; Roppolo, I.
Abstract This work reports the formulation of vinyl ether containing functionalized graphene sheets in order to produce UV‐curable conductive inks. The best graphene‐surfactant ratio was found to give a stable dispersion of graphene into triethyleneglycol divinyl ether (DVE3) resin, avoiding the presence of large filler aggregates that could clog printing head during ink‐jet process. Propylene carbonate was used as solvent to adjust the viscosity of the formulation. The presence of graphene did not significantly hindered the UV‐curing process. Crosslinked nanocomposite materials show a decrease of resistivity of seven order of magnitude with respect to the pristine polymeric matrix.<inline-graphic xlink:href="ark:/27927/pgj9kx2r7g" content-type="mame201400269-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />